Predicting liver ablation volumes with real-time MRI thermometry - Öcal, Osman; Dietrich, Olaf; Lentini, Sergio; Bour, Pierre; Faller, Thibaut; Ozenne, Valery; Maier, Florian Maximilian; Fabritius, Matthias P.; Puhr-Westerheide, Daniel; Schmidt, Vanessa F.; Öcal, Elif; Seidensticker, Ricarda; et al. (JHEP reports, 2024)
Background & Aims - MRI guidance offers better lesion targeting for microwave ablation of liver lesions with higher soft-tissue contrast, as well as the possibility of real-time thermometry. This study aims to evaluate the correlation of real-time MR thermometry-predicted lesion volume with the ablation zone in postprocedural first-day images. - Methods - This single-center retrospective analysis evaluated prospectively included patients who underwent MRI-guided microwave ablation with real-time thermometry between December 2020 and July 2023. All procedures were performed under general anesthesia on a 1.5 T MRI scanner. Real-time thermometry data were acquired using multi-slice gradient-echo echoplanar imaging sequences, and thermal dose maps (CEM43 of 240 min as a threshold) were created. The volume of tissue exposed to a lethal thermal dose in MR thermometry (thermal dose) was compared with the ablation zone volume in portal phase T1w MRI on the postprocedural first day using the Pearson correlation test, and visual quantitative assessment by radiologists was performed to evaluate the similarity of shapes and volumes. - Results - Out of 30 patients with 33 lesions with thermometry images, six (18.1%) lesions were excluded because of artifacts limiting interpretation of thermal dose volume. Twenty-four patients with 27 lesions (20 male, age 63.1 ± 9.1 years) were evaluated for the volume correlation. The volume of thermal dose-predicted lesions and the postprocedural first-day ablation zones showed a strong correlation (R = 0.89, p <0.001). Similarly, visual similarity of molecular resonance thermometry-predicted shape and the ablation zone shape was graded as perfect in 23 (85.1%) lesions. - Conclusions - Real-time thermal dose-predicted volumes show very good correlation with the ablation zone volumes in images obtained 1 day after the procedure, which could reduce the local recurrence rates with the possibility of re-ablating lesions within the same procedure. - Impact and implications: - Heat-based ablation is an established treatment for liver tumors; however, there is a considerable rate of incomplete treatment because of the lack of real-time visualization of the treated area during treatment. Our results show that MRI-guided ablation enables the visualization of the treatment area in real-time with high accuracy using a special technique of MR thermometry in patients with liver tumors.
Gesehen am 28.04.2025